Movie Recommender Chatbot Based on Kansei Engineering - Lin, Pei-Chun (Journal of Soft Computing and Data Mining, 2020)
This paper proposes a recommender system based on Kansei model to solve the trivial things around life which gives support and reference for people who can’t decide things. The Kansei algorithm design is introduced in the developed system. Taking the recommended movie as an example, the user’s preference is guessed by analyzing the relevant information of the movie and the relevant information of the user, thereby catering to the user’s preference and achieving the recommendation purpose. A chat robot interface, cross-platform synchronization information, and easy-to-follow text communication are the main features of the system which allows people to communicate conveniently with the robot and assist them to solve the problem or decide a thing.